Reevaluation of possible outcomes of infections with human immunodeficiency virus. (April 2016) - Tamalet, C.; Colson, P.; Decroly, E.; Dhiver, C.; Ravaux, I.; Stein, A.; Raoult, D.
Abstract: Several lines of evidence indicate that HIV infection can result in several possible incomes, including a very small proportion of individuals whose HIV replication is controlled after treatment interruption (known as HIV posttreatment controllers) or spontaneously without any treatment (known as HIV elite controllers). Both types of individuals are HIV RNA negative but HIV DNA positive, with living virus which can be stimulated ex vivo. A review was conducted to assess the literature on yet rarer cases with detectable integrated HIV DNA without HIV infectious virus in HIV-seropositive or -negative individuals. Three categories of patients were identified: (a) HIV-seropositive individuals with apparent spontaneous cure from their HIV infection, (b) HIV-seronegative children born to HIV-infected mothers and (c) highly exposed seronegative adults. Validity criteria were proposed to assess the presence of integrated HIV DNA as possible or unquestionable in these three categories. Only three articles among the 22 ultimately selected fulfilled these criteria. Among the highly exposed seronegative subjects, some individuals were described as being without integrated HIV DNA, probably because these subjects were not investigated using relevant, highly sensitive methods. Finally, we propose a definition of spontaneous cure of HIV infection based on clinical, immunologic and virologic criteria.